Using mechanical and thermodynamic methods to evaluate the effects of nanomaterials on thermal cracking mechanisms of asphalt mixtures under the influence of different moisture conditions - Amir Hossein Asadi; Gholam Hossein Hamedi; Alireza Azarhoosh (Case Studies in Construction Materials)
Hot mix asphalt (HMA) is often exposed to moisture. Water in the bitumen-aggregate system leads to various HMA damages in the form of adhesive (failure at the bitumen-aggregate contact surface) and cohesive (failure in the mastic phase). The main part of the moisture entering the HMA is the runoff containing dust, soot, and other surface contaminations, which affect the acidity or basicity of runoff and failure severity. In chemistry, acidity or basicity historically denotes the potential or power of hydrogen (pH). Nevertheless, most of the studies into the effect of moisture with various pH on HMA performance deal with fatigue failure and moisture damage, and only a few studies have evaluated the thermal cracking of HMA. Given the occurrence of thermal cracking as the adhesive and cohesive failures, the current study evaluated the effect of acidic, basic, and neutral moisture conditions on the cohesion and adhesion performance of the bitumen-aggregate system at low temperatures using mechanical and thermodynamic methods. The thermodynamic approach based on the chemical and molecular properties of HMA components, along with mechanical methods, can provide a better vision of the causes and factors affecting the occurrence of thermal cracking in the form of adhesive and cohesive failure. Considering the unique properties of multi-walled carbon nanotubes (MWCNTs) and nano-graphene oxide (NGO), including hydrophobicity, high tensile strength, high modulus of elasticity, and effective outcomes in water treatment industries, these two materials were utilized as bitumen additives at 0.3 and 0.6 % by weight of bitumen to improve the low-temperature performance of bitumen and aggregates against adhesive and cohesive failures under various moisture conditions. The pull-off test was performed in two states of adhesive and cohesive failures on various bitumen-aggregate combinations under moisture conditions with different pH levels. Moreover, the surface free energy (SFE) components of bitumens and aggregates were measured using the Wilhelmy plate method and universal sorption device, respectively, and the relevant SFE parameters were calculated. Based on the pull-off test and statistical analysis results, moisture conditions with different pH levels, especially acidic, significantly reduced the adhesive and cohesive strength of the bitumen-aggregate system at low temperatures. In contrast, utilizing MWCNTs and NGO and increasing their weight percentage, especially that of NGO, significantly increased the adhesion pull-off and cohesion pull-off at low temperatures under acidic, basic, and neutral moisture conditions. Based on the SFE results, by increasing or decreasing the pH of water, the debonding energy (DE) of bitumen and aggregate was raised, and, therefore, the adhesive failure potential increased. Meanwhile, MWCNTs and NGO increased the resistance of the bitumen-aggregate system against cohesive and adhesive failures by raising the bitumen's cohesion free energy and the bitumen-aggregate DE under different moisture conditions. According to the mechanical and thermodynamic tests, acidic water with pH= 5 was the most destructive moisture condition, diminishing the bitumen's cohesive strength and the bitumen-aggregate adhesive strength at low temperatures. Furthermore, 0.6 % NGO showed the best performance in reducing the thermal cracking potential as cohesive and adhesive failures.